The Director as Ethical Mediator: Institutional Documentary Practice in Rumah Kejujuran - Wida Kurnianda Djamil; Petrus Damiami Sitepu (Universitas Multimedia Nusantara, 2026)
This research explores how the ethics can be preserved in institutional documentary practice by the conception of the director as an ethical intermediary. The research uses a qualitative, practice-based approach and focuses on a collaborative project between UMN and KPK called Rumah Kejujuran on the basis of a documentary. It is the process of creative work that will be the principal object of investigation and the primary source of data. As a practitioner-researcher, the director will have to reflect on ethical considerations during the entire production process. There are all phases of documentary film making that are used to gather data: development until post-production. Such data include audiovisual information, anecdotal commentaries and subjective access to the subject, and institutional records of production limitations. Reflective interpretative analysis of the data is done using thematic interpretation including the tension of ethics, creative negotiation, humanistic representation and institutional constraint. The results demonstrate that the ethical issues are mainly brought about by structural circumstances to define what is possible to be represented, but not through direct interventions. Imaginative bargaining in documentary mode, narrative format, and visual characteristics helps in maintaining morality. The analysis shows that by depicting the subjects as social actors in daily situations, humanistic representation does not allow the decrease of the subjects to the status of institutional symbols. The study redefines institutional documentary practice as a reflective and ethical negotiation space by framing the filmmaking process as an ethical space.